NSUN2/ALYREF axis-driven m5C methylation enhances PD-L1 expression and facilitates immune evasion in non-small-cell lung cancer - Yiran Yang; Leiqun Cao; Xin Xu; Dan Li; Yuan Deng; Li Lan; Bingjie Zeng; Haixia Jiang; Shan Liang; Yiwen Huang; Yunhua Xu; Lifang Ma (2025)
Non-small-cell lung cancer (NSCLC) represents a highly prevalent form of malignancy. 5-methylcytosine (m5C) methylation functions as a key post-transcriptional regulatory mechanism linked to cancer progression. The persistent expression of PD-L1 in tumor cells plays a pivotal role in facilitating immune evasion and promoting T-cell exhaustion. However, the involvement of m5C in NSCLC immune evasion remains inadequately understood. This study seeks to explore the function of the m5C methyltransferase NSUN2 in modulating PD-L1 expression and facilitating immune evasion in NSCLC. Our findings indicate elevated levels of NSUN2 and ALYREF in NSCLC, and both promote the growth of NSCLC cells and the progression of lung cancer. Moreover, the expression of PD-L1 in NSCLC tissues positively correlates with NSUN2 and ALYREF expression. We then discovered that PD-L1 acts as a downstream target of NSUN2-mediated m5C modification in NSCLC cells. Knocking down NSUN2 significantly reduces m5C modification of PD-L1 mRNA, thereby decreasing its stability via the m5C reader ALYREF-dependent manner. Furthermore, inhibiting NSUN2 enhanced CD8+ T-cell activation and infiltration mediated by PD-L1, thereby boosting antitumor immunity, as confirmed in both in vitro and in vivo experiments. Collectively, these results suggested that NSUN2/ALYREF/PD-L1 axis plays a critical role in promoting NSCLC progression and tumor cell immune suppression, highlighting its potential as a novel therapeutic strategy for NSCLC immunotherapy.